Semoga hijrahku abadi : kutemui cinta sejati - Abdul Malek Md. Noor, Datuk, 1954-; Raihanah Abdullah; Rohani Pa' Wan Chik (Kuala Lumpur : Berita Publishing, 2012)
Autobiography of Datuk Malek Noor, a Malaysian bodybuilder, actor, and businessman.
In Malay.
Keywords: Malek Noor, -- Datuk, -- 1954-.; Bodybuilders -- Biography; Sports -- Biography; Businessman -- Malaysia -- Biography